Combination of Eucheuma Cottonii and Corticosteroids has a Superior Immunomodulatory Effect on Asthma - Rizaldy, Rheza; Mulyani, Sri Priantini; Sumarawati, Titiek (Poltekkes Kemenkes Palu, 2023)
Asthma prevalence has been increasing globally which is commonly treated using corticosteroid as gold standard treatment. However, corticosteroids have adverse effects and cases of corticosteroid-resistant asthma are emerging. Eucheuma cottonii (EC) has been shown to potentially attenuate inflammatory response in type I hypersensitivity. This study aimed to investigate the effect of Eucheuma cottonii extract and methylprednisolone combination on IL-4, IL-10, and histamine levels in Ovalbumin-induced asthma BALB/c mice. Thirty female BALB/c mice were randomly assigned to 6 groups : (1) Sham; (2) Ovalbumin-induced asthma mice; (3) Ovalbumin-induced asthma mice treated with methylprednisolone (MP) 0.24 mg/day; (4) Ovalbumin-induced asthma mice treated with EC extract 300 mg/kgBW/day; (5) Ovalbumin-induced asthma mice treated with combination of both. Treatments were given respectively for 7 days. Plasma IL-4, IL-10, and histamine levels were measured using ELISA method. The combination group showed both the lowest IL-4 levels (89.30 ± 1.37 pg/ml) and the highest IL-10 levels (487.03 ± 20.57 pg/ml) compared to other asthma-like mouse groups (p = 0.001). No significant difference was observed in histamine levels among all treatments (p > 0.05). The administration of a combination of methylprednisolone and Eucheuma cottonii extract significantly affected plasma IL-4 and IL-10 levels compared to monotherapies. However, there was no significant difference in plasma histamine levels compared to monotherapies.